Hubungan Intensitas Gadget, Pola Asuh, Dengan Perkembangan Bahasa Dan Bicara Anak Usia Pra-sekolah Di PAUD Terpadu Mokusato : (The Relationship between Gadget Intensity, Parenting Patterns, and the Development of Language and Speech in Preschool-Age Children at Mokusato Integrated Preschool - Surate, Inggrid Permatasari Putri; Novita (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Data from the Central Statistics Agency (2020) shows that 29% of all gadget use is at an early age and 25,9% of them are toddlers. While children who use the internet are 0,93% infants and 10,71% toddlers. are three times more likely to have a language delay. Parenting is a pattern of behavior that is applied to children and is relatively consistent from time to time. Santrock (2021) divides parenting into three types, namely authoritative, authoritarian, and permissive. Even though the parenting styles are different, parents should know that the attitudes and behavior displayed by parents are inseparable from the attention and observation of the child, because during their development, children always want to obey what their parents do better known as imitating.  Methods: The quantitative research design uses a cross-sectional approach the sample in this study were all students aged 3-6 years who attended the Mokusato Integrated Early Childhood Education as many as 43 students. The sampling technique was total sampling.  Results: The results showed that out of 43 respondents, there were 10 respondents (100,0%) who were light gadget users, 17 respondents (100,0%) were moderate gadget users, and 16 respondents (100,0%) were heavy gadget users. Hypothesis testing using the chi-square Test obtained a p-value of 0,006 (p < 0,05). The results showed that of the 43 respondents who applied good parenting, 32 respondents (100,0%) and 11 people (100,0%) were not good. Hypothesis testing using the chi-square Test obtained a p-value of 0,000 (p < 0,05).  Discussion: There is a significant relationship between Gadget Intensity, parenting style, and delays in speech and language development in preschool-aged children at the Mokusato Integrated Preschool.